2008
DOI: 10.1074/jbc.m708799200
|View full text |Cite
|
Sign up to set email alerts
|

p66 Inhibits Pro-survival Epidermal Growth Factor Receptor/ERK Signaling during Severe Oxidative Stress in Mouse Renal Proximal Tubule Cells

Abstract: The fully executed epidermal growth factor receptor (EGFR)/ Ras/MEK/ERK pathway serves a pro-survival role in renal epithelia under moderate oxidative stress. We and others have demonstrated that during severe oxidative stress, however, the activated EGFR is disconnected from ERK activation in cultured renal proximal tubule cells and also in renal proximal tubules after ischemia/reperfusion injury, resulting in necrotic death. Studies have shown that the tyrosine-phosphorylated p46/52 isoforms of the ShcA fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 40 publications
1
84
0
Order By: Relevance
“…Earlier work of Safirstein, Heyman, Rosen, and others showed that the distal nephron can respond to a variety of injuries by expressing cytokines (114) and growth factors (115), activating ERK (116) and HIF (117), and redistributing corticomedullary circulation (118). Using mouse models, we showed that various injuries induce a cell-specific response in the CD, namely the activation of A-ICs (15).…”
Section: Figurementioning
confidence: 88%
“…Earlier work of Safirstein, Heyman, Rosen, and others showed that the distal nephron can respond to a variety of injuries by expressing cytokines (114) and growth factors (115), activating ERK (116) and HIF (117), and redistributing corticomedullary circulation (118). Using mouse models, we showed that various injuries induce a cell-specific response in the CD, namely the activation of A-ICs (15).…”
Section: Figurementioning
confidence: 88%
“…Kidneys were removed and homogenized in a RIPA buffer as described earlier (2). Similarly, monolayers of cells were lysed in a RIPA buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, in this study, overexpression of a phosphorylation-defective p66 Shc mutant protein in INS-1E cells did not affect basal and reduced palmitate-induced apoptosis, respectively. Depending on the cellular context and stimulus, Ser 36 phosphorylation of p66 Shc was found to be promoted by either the MAP kinases ERK-1/2 or the stressactivated kinases JNK and p38 MAPK [14,15,35,[38][39][40][41][42]. In specific cells, it was shown to be mediated by PKCβ activation [43][44][45].…”
Section: Discussionmentioning
confidence: 95%
“…p66 Shc possesses specific functions, such as modulation of p46/52 Shc complex activation and downstream signalling via MAPK kinase (MEK)-extracellular signal-regulated kinase (ERK) [13][14][15][16] and control of actin cytoskeleton turnover and glucose transport [16,17]. Importantly, p66 Shc is implicated in both sensing and activation of cellular oxidative stress and consequent induction of apoptosis [18].…”
Section: Introductionmentioning
confidence: 99%